Counteracting fake news as a factor in the development of professional competencies of future journalism students - Rufina Torpichsheva; Elena Burdina; Albina Anesova; Nataliia Fominykh; Maiya Kayumova (Institute of Advanced Engineering and Science, 2026)
The purpose of this study is to assess the impact of training in countering fake news on the development of professional competencies among journalism students. This research provides a structured pedagogical framework for teaching fact-checking and critical thinking. Using a quasi-experimental design at Toraighyrov University (n=190), the study compared an experimental group (EG) with a control group (CG) across three phases: diagnostic, instructional, and evaluative. Results from the 2024 final testing demonstrate significant efficacy: the EG showed a 64% increase in critical thinking, news analysis, fact-checking, vastly outperforming the 11% growth in the CG. Qualitative data further confirmed a marked reduction in trust toward unverified sources. These findings offer a scalable model for journalism education, proving that targeted instructional interventions are highly effective for developing professional competencies in media content evaluation.